Flexural strengthening of RC beams with BFRP or high strength steel bar–reinforced ECC matrix. (11th October 2021) - Li, Zhi-qiang; Hou, Wei; Lin, Guan
Highlights: The effects of BFRP and HSS bars reinforced ECC as the strengthening layer were compared and evaluated to improve the flexural behavior of RC beams. The difference between the two strengthening systems confirmed the excellent strain compatibility of BFRP bars and ECC matrix. The advantages of ECC due to its high ultra-high ductility and crack control capability over polymer mortar as the matrix of the strengthening layer are obvious. The proposed analytical model predicted the flexural load response and failure modes accurately. Abstract: This paper has investigated the flexural behavior of reinforced concrete (RC) beams strengthened with BFRP (basalt fiber reinforced polymer) or HSS (high strength steel) bar reinforced ECC matrix. A total of six strengthened RC beams and one control RC beam were tested under four-point bending up to their failure. The test variables included the cement matrix (ECC and polymer mortar), the reinforcements type (BFRP and HSS bars) as well as the reinforcement ratio (0.94% and 1.41%) of the strengthening layer. Two failure modes including the rupture of BFRP bars and the rupture of ECC matrix followed by the slippage of the steel bars were obtained in the strengthened beams. The rupture of BFRP bars dominated the failure of beams strengthened with BFRP bar reinforced cement matrix owing to the limited tensile strength of BFRP bars, and the percentage of enhancement in flexural capacity ranged from 18.6% to 47.8% compared with the control beam. The beams strengthened with HSS bar reinforced ECC matrix all failed due to the rupture of ECC matrix followed by the slippage of HSS bars, mainly owing to the high stiffness and strength of the HSS bars, leading to larger enhancements in flexural capacity at a range of 60.0–75.6%. In addition, a beam strengthened with BFRP bar reinforced polymer mortar was also tested with the purpose of conforming the advantage of ECC over polymer mortar as the matrix of the strengthening layer. The test results showed that the application of ECC matrix with BFRP bars resulted in larger enhancement in the yield and ultimate loads compared to the use of polymer mortar matrix. The difference between the two strengthening systems confirmed the excellent strain compatibility of BFRP bars and ECC matrix. Finally, a flexural theoretical analysis based on three possible failure cases was proposed, and its reliability was verified through comparing the test results and the theoretical predictions.